Potential of crude seed extract of celery, Apium graveolens L., against the mosquito Aedes aegypti (L.) (Diptera: Culicidae) - Choochote W. (2014)
Crude seed extract of celery, Apium graveolens, was investigated for anti-mosquito potential, including larvicidal, adulticidal, and repellent activities against Aedes aegypti, the vector of dengue haemorrhagic fever. The ethanol-extracted A. graveolens possessed larvicidal activity against fourth instar larvae of Ae. aegypti with LD50 and LD95 values of 81.0 and 176.8 mg/L, respectively. The abnormal movement observed in treated larvae indicated that the toxic effect of A. graveolens extract was probably on the nervous system. In testing for adulticidal activity, this plant extract exhibited a slightly adulticidal potency with LD50 and LD95 values of 6.6 and 66.4 mg/cm2, respectively. It showed repellency against Ae. aegypti adult females with ED50 and ED95 values of 2.03 and 28.12 Mg/cm2 , respectively. It also provided biting protection time of 3 h when applied at a concentration of 25 g%. Topical application of the ethanol-extracted A. graveolens did not induce dermal irritation. No adverse effects on the skin or other parts of the body of human volunteers were observed during 3 mo of the study period or in the following 3 mo, after which time observations ceased. A. graveolens, therefore, can be considered as a probable source of some biologically active compounds used in the development of mosquito control agents, particularly repellent products.